High Levels of CXCL8 and Low Levels of CXCL9 and CXCL10 in Women with Maternal RhD Alloimmunization - Schettini, Juliana Araújo de Carvalho; Gomes, Thomás Virgílio; Santos Barreto, Alexandra Karla; da Silva Júnior, Claudeir Dias; da Matta, Marina; Coutinho, Isabela Cristina Neiva; de Oliveira, Maria do Carmo Valgueiro Costa; Torres, Leuridan Cavalcante (Frontiers in Immunology, 2017)
Abstract Maternal RhD alloimmunization is an inflammatory response against protein antigens in fetal red blood cells (RBC). However, not all women become alloimmunized when exposed to RhD+ fetal RBC. Thus, this study aimed to evaluate levels of inflammatory chemokines in RhD- pregnant women with erythrocyte alloimmunization. CXCL8, CXCL9, CCL5, and CXCL10 levels were determined from cell culture supernatants by flow cytometry in 46 (30 non-alloimmunized RhD− and 16 previously alloimmunized RhD−) pregnant women. CXCL8 levels were significantly higher (P<0.004) and CXCL9 (P<0.008) and CXCL10 (P<0.003) levels were significantly lower in alloimmunized pregnant women. No significant difference in CCL5 levels was detected between the groups. Fetal RHD genotyping was performed in the alloimmunized RhD− group by real-time PCR. Anti-D alloantibody was detected in 10 mothers and anti-D and -C in six mothers. Twelve fetuses were RHD positive and four were RHD negative. Further studies of serum chemokines and placenta tissue could provide a better understanding of the cells involved in the pathogenesis of maternal erythrocyte alloimmunization. Key words: chemokines, pregnancy, inflammation, flow cytometry, Rh(o) antigen, genotyping techniques, hemolytic disease of the fetus and newborn.